Fertility preservation in gynaecology oncology patients: Experience from an Australian tertiary oncology centre. (15th February 2022) - Robson, Danielle; de Vries, Bradley; Pather, Selvan; Marren, Anthony
Abstract : Background: Management for gynaecological cancers often includes removal of the reproductive organs and/or the use of gonadotoxic therapies resulting in sub‐fertility. Oncofertility and discussion of fertility preservation in these patients is critical. Aim: To determine the rate of fertility preservation discussion among a cohort of patients with a gynaecological cancer and what determinants impact likelihood of a discussion. Materials and Methods: A seven‐year quantitative retrospective study was conducted at a single oncology centre, including 15–45 year old patients with a gynaecological cancer. The primary outcome was if a fertility preservation discussion occurred during a consultation. Secondary outcomes included if a referral was made and what fertility preservation services were undertaken. Determinants that impacted the likelihood of a fertility preservation discussion were analysed. Results: One hundred and twenty‐one patients were analysed. There were 84 (69%) patients who had a documented fertility preservation discussion, and 46% were referred to a fertility specialist for consultation. Age was a significant determinant, with patients aged 30–39 years of age more commonly having a fertility preservation discussion. Patients with a high‐grade cancer compared to patients with a lower‐grade cancer (grade one or two) were only a third as likely to have a discussion surrounding their fertility (odds ratio: 0.33, 95% CI: 0.13–0.86; P = 0.02). Conclusion: We conclude that rates of discussion around fertility options for patients with cancer are lower than the recommended guidelines. Oncofertility is an important discipline which we believe needs to be emphasised within the gynaecology oncology community and management of patients should include a multi‐disciplinary team.